2016
DOI: 10.5194/bg-13-2959-2016
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the carbon budget of a pasture: effect of system boundaries and flux uncertainties

Abstract: Abstract. Carbon (C) sequestration in the soil is considered as a potential important mechanism to mitigate greenhouse gas (GHG) emissions of the agricultural sector. It can be quantified by the net ecosystem carbon budget (NECB) describing the change of soil C as the sum of all relevant import and export fluxes. NECB was investigated here in detail for an intensively grazed dairy pasture in Switzerland. Two budget approaches with different system boundaries were applied: NECB tot for system boundaries includi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Over the study period, the site experienced large variations in temperature, moisture availability, and radiation, which are controlling factors of the exchange rates between the atmosphere and grasslands of CO 2 [87][88][89][90] and water fluxes [91]. In addition, grazing and cutting dramatically alter the way managed grassland ecosystems respond to climate drivers by the sharp removal of large amounts of live biomass [36,92,93] and thus strongly affect the seasonal and inter-annual variabilities of gas exchanges and the annual carbon budgets of the farm/paddock [22,79,94].…”
Section: Performances Of the Cenw Model To Simulate Gas Exchanges Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the study period, the site experienced large variations in temperature, moisture availability, and radiation, which are controlling factors of the exchange rates between the atmosphere and grasslands of CO 2 [87][88][89][90] and water fluxes [91]. In addition, grazing and cutting dramatically alter the way managed grassland ecosystems respond to climate drivers by the sharp removal of large amounts of live biomass [36,92,93] and thus strongly affect the seasonal and inter-annual variabilities of gas exchanges and the annual carbon budgets of the farm/paddock [22,79,94].…”
Section: Performances Of the Cenw Model To Simulate Gas Exchanges Of mentioning
confidence: 99%
“…In this study, we showed that the direct effect of grazing (i.e., the reduction of photosynthesizing biomass [22]) was properly captured in EC data but that the indirect effect (i.e., grazing animals' respiration [22]) was not captured by EC systems because of the stochastic position of cows and shifts in the flux footprint area. To fully understand why grazers' respiration is not accounted for and to find a way to correct EC data for this bias, using a biochemical, process-based ecosystem model incorporating management practices, like CenW, alongside dairy cows positioning devices and detailed flux footprint information, could be necessary [79,94].…”
Section: Cow Respiration In Observed and Modeled Co 2 Fluxesmentioning
confidence: 99%
“…representative way suggesting that there were no correlations between the animal positions and the 109 wind direction. However, this result is site specific and such observations has yet to be verified for 110 continuously grazed pastures (Felber et al, 2016a). In those sites the animals are allowed to move 111 freely in the pasture so that, if cattle are more likely to remain grouped in specific areas of the pasture 112 such as shade areas or near water/feed supplies, which is very probable, NEE tot would be biased in a 113 way and to an extent that depends on the position of these specific areas relative to the footprint.…”
Section: Abstract 27mentioning
confidence: 88%
“…He proposed to filter out the fluxes from paddocks affected by cattle respiration, compute 95 NEE past , and account for the biomass ingested by the animals as C exports and the animal excretions as 96 C imports, thereby considering cattle to be external to the system. More recently, several studies also 97 identified this problem and adapted their methodology to exclude grazer respiration and thus, compute 98 NEE past (Felber et al, 2016a;Hunt et al, 2016;Rutledge et al, 2017aRutledge et al, , 2017b. Kirschbaum et al, 99 (2015) also highlighted the need to filter fluxes in the presence of high stocking density in the 100 footprint in order to obtain good agreement between modelled and measured CO 2 fluxes in a 101 rotationally grazed pasture.…”
Section: Abstract 27mentioning
confidence: 99%
See 1 more Smart Citation